IMPLEMENTASI KEBIJAKAN PENGEMBANGAN OBJEK WISATA SELAT LEMBEH KECAMATAN LEMBEH SELATAN KOTA BITUNG - Mex Iver Mapahena; Agustinus B. Pati; Deysi ., Tampongangoy (AGRI-SOSIOEKONOMI, 2021)
The purpose of this study is to describe and analyze the implementation of the policy for the development of the Lembeh Strait tourism object, South Lembeh District, Bitung City. as well as to determine the factors supporting and inhibiting the implementation of the policy. The research method used in this study is a qualitative descriptive. Data collection techniques used are interviews, observations and documents The theory used is the Van Meter and Van Horn implementation model, the model consisting. The research informants were 15 people. The results showed that the implementation of the Lembeh Strait tourism object development policy, South Lembeh District, Bitung City has not been carried out properly due to the difficulty of establishing communication with the surrounding community in terms of cooperation in maintaining and supporting development facilities and the implementation of planned activities. In implementing this policy, human resources are still experiencing obstacles. Inadequate and ineffective coordination with other agencies is caused by the agency's own department, and the agency assumes itself that this development task is only the task of the related institutions.T